Antimicrobial activity of three hard coral species from South China Sea (Malaysia) - Qaralleh, Haitham; Idid, Syed Zahir; Saad, Shahbudin; Susanti , Deny; Althunibat, Osama Yousef; Sheikh, Hasan I (SYLWAN Journal, 2014)
The problem of antimicrobial drug resistance has necessitated a search for new antimicrobial substances from other sources including natural sources. Marine organisms are known to produce metabolites to protect themselves against pathogens and therefore can be considered as a potential source of antimicrobial substances. This study designed to evaluate the antimicrobial activity of three hard coral species namely Favites sp Link (Faviidae), Galaxea fascicularis Linnaeus (Oculinidae), and Galaxea astreata Lamarck (Oculinidae) against six pathogenic microbes. The coral species were extracted with water and a combination of dichloromethane and methanol. The antimicrobial activity of the extracts was evaluated using disc diffusion method and microdilution method. From the disc diffusion method, the organic extracts showed antimicrobial activity while the aqueous extracts showed no activity. The organic extract from G. fascicularis was the most effective against Staphylococcus aureus (11 mm) and Bacillus cereus (10.5 mm). From the microdilution method, the organic extracts of G. fascicularis and G. astreata showed inhibitory effect against S. aureus and B. cereus at low concentrations (0.003 - 0.1 mg/mL). However, complete growth inhibitions of S. aureus and B.cereus were observed for the organic extract of G. fascicularis at concentrations of 0.34 and 1.1 mg/mL, respectively. Further studies must be conducted to isolate the antimicrobial compounds from the G. fascicularis, which may contribute towards finding compounds for the treatment of infectious diseases.